2007
DOI: 10.1017/s0001924000004905
|View full text |Cite
|
Sign up to set email alerts
|

Remarks on the nonlinear dynamics of a typical aerofoil section in dynamic stall

Abstract: Figure 1. Static (dashed line) and dynamic (solid line) aerodynamic forces and moments of an aerofoil in pure pitching oscillation.The numbers refer to key dynamic stall events described in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Ocokoljić, et al investigated the requirements for the accuracy of measurements in a wind tunnel, such as calibration of the wind tunnel test section [12]. Other relevant studies have also focused on stall-induced vibration analysis [13,14], bifurcation and chaos analysis [15][16][17], non-linear dynamics [18], and stability analysis [19]. It could be concluded that one of the main objectives of all studies in this field is to develop a reliable, precise, and fast method for aero-elastic behavior, stability, and the flutter speed analysis while avoiding numerical integration issues of instability and inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Ocokoljić, et al investigated the requirements for the accuracy of measurements in a wind tunnel, such as calibration of the wind tunnel test section [12]. Other relevant studies have also focused on stall-induced vibration analysis [13,14], bifurcation and chaos analysis [15][16][17], non-linear dynamics [18], and stability analysis [19]. It could be concluded that one of the main objectives of all studies in this field is to develop a reliable, precise, and fast method for aero-elastic behavior, stability, and the flutter speed analysis while avoiding numerical integration issues of instability and inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of analyses of stall-induced vibrations are carried out by time integration of the ODEs representing the aeroelastic system with a variety of semi-empirical dynamic stall models such as the ONERA 1 (Sarkar and Bijl, 2008;Mahajan et al, 1993), Gormont (Li and Fleeter, 2003), Leishman-Beddoes (Price and Fragiskatos, 2000;Galvanetto et al, 2007) or Gangwani (Price and Keleris, 1996) models to name but a few. However, such an approach is computationally unaffordable for the purposes of this study.…”
Section: Introductionmentioning
confidence: 99%